WAYS TO INCREASE THE INCOME OF THE POPULATION DURING ECONOMIC TRANSFORMATION - Uzokov S.D. (PEDAGOGS, 2025)
Economic transformation often brings about shifts in industries, technological advancements, and structural changes that can reshape how wealth is distributed in a society. As economies transition from one phase of development to another—whether through industrialization, digitalization, or green energy initiatives—it is vital to implement strategies that ensure the population's income does not stagnate or worsen. Increasing the income of the population during these times of transformation requires a combination of forward-thinking policies, strategic investments, and social programs.